Plasmonics: Nanoscale Imaging and Spectroscopy of Plasmonic Modes with the PTIR Technique (Advanced Optical Materials 8/2014). Issue 8 (August 2014) - Katzenmeyer, Aaron M.; Chae, Jungseok; Kasica, Richard; Holland, Glenn; Lahiri, Basudev; Centrone, Andrea
<x xml:space="preserve">Abstract</x> An atomic force microscopy (AFM) tip is used to provide local absorption maps and spectra of plasmonic resonators in the mid‐IR. On page 718, A. Centrone and co‐workers use photothermally induced resonance (PTIR) to combine the lateral resolution of AFM, enabling the measurement of light absorption at a length scale several times smaller than the light diffraction limit. Since the PTIR signal is not affected by scattering, PTIR spectra are free of Fano spectral distortions typically observed in the far‐field. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>